MENINGKATAN MUTU PEMBELAJARAN MELALUI SUPERVISI AKADEMIK DI SMKN 1 CIKAMPEK TAHUN PELAJARAN 2018/2019 - MAKMUR, MAKMUR (Pedagogiana : Jurnal Pendidikan Dasar, 2021)
The success of education in educational units is strongly influenced by the role of the principal as a researcher in the learning leadership of teachers. The principal in the education unit has a strategic role in determining the success and failure of teachers in learning in which there is a learning evaluation system. the author is interested in conducting School Action Research (PTS) entitled "Improving the Quality of Learning Through Academic Supervision at Smkn 1 Cikampek". Based on the background of the problems that have been described, the problems that arise can be identified by the authors as follows: 1) The low interest in student learning, as evidenced by the results of daily test scores that do not meet the KKM; 2) Only 15% of students have a high interest in learning, as evidenced by the number of library visitors on average 70 to d. 80 students/day; 3) Only 35% of students have moderate interest in learning, as evidenced by the number of students who submit practical/cocurricular assignments less than half the number of students per class; and 4) Only 65% ​​of students have low interest in learning. So, the authors set several formulations of the problem, among others; 1) Can the academic supervision of teachers improve their performance?; 2) Can academic supervision change the interest and willingness to carry out good learning in accordance with the rules and steps of the teaching and learning process?, 3) Can this supervision change the learning culture in the classroom to be better with active, creative, effective and effective learning patterns? pleasant?. An activity is impossible without a goal. Likewise, this research was carried out with the objectives of: 1) Improving the quality of student learning; 2) Increase students' interest in learning 3) Improve the ability of teachers in the implementation of learning so that it is in accordance with predetermined standards. The results of the presentation of success in cycle 1 are the average success of planning 71.98%, implementation 72.44%, assessment 81.3%, and follow-up 59.76%, while in cycle II the average success of planning is 92.44% , 93.81% implementation, 90.56% assessment, and 83% follow-up.